Preparation and bifunctional properties of the A-site-deficient SrTi0.3Fe0.6Ni0.1O3−δ perovskite. Issue 52 (25th November 2022) - Xu, Na; Zhang, Jiyuan; Su, Shaohui; Feng, Jingdong; Xu, Zhanlin
Abstract : The development of efficient, non-noble metal electrocatalysts for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) is crucial for their application in energy storage devices, such as fuel cells and metal–air batteries. Abstract : The development of efficient, non-noble metal electrocatalysts for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) is crucial for their application in energy storage devices, such as fuel cells and metal–air batteries. In this study, SrTi0.3 Fe0.6 Ni0.1 O3− δ (STFN) perovskite was synthesized using the sol–gel method, and its electrocatalytic activity was evaluated using a rotating disk electrode (RDE) in an alkaline medium. STFN synthesized at the optimum synthesis temperature of 800 °C exhibited good ORR and OER performances. To further improve electrocatalytic activity, a series of Sr1− x Ti0.3 Fe0.6 Ni0.1 O3− δ ( x = 0, 0.05, and 0.1) perovskites with A-site vacancies were synthesized at 800 °C. Material characterization results showed that the removal of the A-site from the perovskite led to an increase in surface oxygen vacancies, resulting in higher ORR and OER activities. The results of this study indicate that Sr1− x Ti0.3 Fe0.6 Ni0.1 O3− δ ( x = 0.1) is a promising bifunctional oxygen electrocatalyst for Zn–air batteries.